Perancangan Aplikasi #JagoNgobrol untuk Meningkatkan Keterampilan Komunikasi Siswa Sekolah Menengah Pertama - Setiawan, Rifki; Praka, Yoseph Satria; Giffary, Danang Aryaputra; Marcheta, Noorlela (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
Effective communication skills are crucial for students' success in the school environment. However, many middle school students still face communication barriers, including a lack of confidence and difficulty articulating their ideas. This study aims to develop the #JagoNgobrol application to enhance students' communication skills through a technology-based approach. The development process includes planning, production design, and evaluation stages. The application is designed with innovative features, including augmented reality simulations, daily mood tracking, mascot customization, and a peaceful nest. Testing results indicate that the application functions well, featuring an interactive interface and multi-level learning materials. The study concludes that #JagoNgobrol has the potential to be a practical solution for improving students' communication skills in a creative and structured manner.